A high-strength permeable brick and preparation method thereof

By using modified diatomaceous earth and silane modified graphene in permeable bricks, the problem of difficult to take into account both the mechanical properties and the wear resistance of existing permeable bricks is solved, and the effect of high strength and excellent wear resistance is achieved.

CN119349944BActive Publication Date: 2025-03-07YONGZHOU XIANGQI CEMENT PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411907818.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-07
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The existing permeable bricks are difficult to take into account both mechanical properties and wear resistance, and there is a problem of insufficient performance.

Method used

The ratio of cement, modified diatomaceous earth, fly ash, gravel, water reducer and water is used to coat the diatomaceous earth with polydopamine and silane modification of graphene to enhance the structural stability and compatibility of the material.

Benefits of technology

It improves the compressive strength, flexural strength and wear resistance of permeable bricks, has good mechanical properties and small grinding pit length.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of building materials, and specifically relates to a high-strength permeable brick and a preparation method thereof. The permeable brick comprises the following raw materials in parts by weight: 25-40 parts of cement, 10-20 parts of modified diatomite, 40-50 parts of fly ash, 60-80 parts of crushed stone, 3-5 parts of water reducer, and 5-10 parts of water; the preparation process of the modified diatomite is as follows: (1) adding the pretreated diatomite to a Tris-dopamine hydrochloride solution for stirring reaction, and obtaining polydopamine-coated diatomite after the reaction is completed; (2) adding graphene to a solvent, and then adding γ-aminopropyltriethoxysilane for heating reaction, and after the reaction is completed, purifying to obtain silane-modified graphene; (3) adding polydopamine-coated diatomite and silane-modified graphene to anhydrous ethanol for stirring, and purifying to obtain modified diatomite. The permeable brick has excellent mechanical properties and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and particularly relates to a high-strength permeable brick and a preparation method thereof. Background Art

[0002] Permeable bricks, also known as seepage bricks, are an environmentally friendly building material that allows rainwater to penetrate directly into the ground through the bricks to replenish groundwater resources. Studies have shown that permeable bricks have the advantages of reducing road surface water, reducing the "heat island effect", and improving the soil environment. They are an indispensable part of promoting the construction of "sponge cities".

[0003] There are three types of commonly used permeable bricks on the market: ceramic permeable bricks, concrete permeable bricks, and sand-based permeable bricks. Among them, although the use of ceramic permeable bricks can reduce the impact of industrial waste on the urban environment, its preparation process is relatively complicated and the cost is high, and the production process will have a certain impact on the environment. Although the preparation process of concrete permeable bricks can reduce the mining of natural sand and gravel, the surface of the brick body is uneven and the performance is poor. The preparation process of sand-based permeable bricks is energy-saving and environmentally friendly, and has excellent performance, so it has become the main production process of permeable bricks. The existing sand-based permeable bricks have technical difficulties in balancing mechanical properties and wear resistance. Based on this, it is necessary to conduct in-depth research on the formula composition of permeable bricks to improve the various properties of permeable bricks and accelerate their application in the field of building materials technology. Summary of the invention

[0004] The first object of the present invention is to provide a high-strength permeable brick with excellent mechanical properties and wear resistance.

[0005] The second object of the present invention is to provide a method for preparing high-strength permeable bricks with simple steps.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A high-strength permeable brick comprises the following raw materials in parts by weight: 25-40 parts of cement, 10-20 parts of modified diatomaceous earth, 40-50 parts of fly ash, 60-80 parts of crushed stone, 3-5 parts of water reducing agent, and 5-10 parts of water;

[0008] The preparation process of the modified diatomite is as follows:

[0009] (1) adding the pretreated diatomaceous earth into a Tris-dopamine hydrochloride solution for stirring reaction, and obtaining polydopamine-coated diatomaceous earth after the reaction is completed;

[0010] (2) adding graphene to a solvent, and then adding γ-aminopropyltriethoxysilane to carry out a heating reaction. After the reaction is completed, filtering, washing, and drying are performed to obtain silane-modified graphene;

[0011] (3) The polydopamine-coated diatomaceous earth obtained in step (1) and the silane-modified graphene obtained in step (2) are added into anhydrous ethanol, stirred, filtered, and dried to obtain modified diatomaceous earth.

[0012] The present invention first adds the pretreated diatomite to a Tris-dopamine hydrochloride solution, and the dopamine molecules are oxidized and self-polymerized in the solution to form polydopamine molecules. The polydopamine has strong adhesion and film-forming properties, and can form a dense coating layer on the surface of the diatomite particles. This coating layer improves the interaction between the diatomite particles and the cement matrix, thereby improving the overall strength of the material. Secondly, the graphene is silane-modified by γ-aminopropyltriethoxysilane, and the modified graphene containing amino groups interacts with the catechol hydroxyl or amino group on the surface of the polydopamine to form hydrogen bonds, which can not only enhance the structural stability of the modified graphene and the polydopamine-coated diatomite mixed system, but also improve the compatibility of the graphene with the cement matrix, reduce the stress concentration phenomenon of the graphene itself, and thus improve the wear resistance of the material.

[0013] Preferably, the solid-to-liquid ratio of the pretreated diatomaceous earth to the Tris-dopamine hydrochloride solution in step (1) is 1 g: (10-20) mL; and the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2-3 g / L.

[0014] Preferably, the pretreatment process of the pretreated diatomaceous earth in step (1) is: adding the diatomaceous earth to a sulfuric acid solution with a concentration of 20-25%, heating it at 70-80° C. for 1.5-3 h, adjusting the pH of the reaction solution to neutral, and drying the reaction solution to obtain the pretreated diatomaceous earth.

[0015] Preferably, the stirring reaction temperature in step (1) is 50-55° C., and the stirring reaction time is 28-32 h.

[0016] Preferably, in step (2), the mass ratio of graphene to γ-aminopropyltriethoxysilane is 1:(0.2-0.3), and the solvent is tetrahydrofuran or cyclohexane.

[0017] Preferably, the temperature of the heating reaction in step (2) is 40-50° C., and the heating reaction time is 6-7 h.

[0018] Preferably, in step (3), the mass ratio of the polydopamine-coated diatomaceous earth obtained in step (1) to the silane-modified graphene obtained in step (2) is 1:(0.05-0.15).

[0019] Preferably, the stirring temperature in step (3) is 40-50° C., and the stirring time is 2-4 h.

[0020] Preferably, the water reducer is a wood sulfonate water reducer or a polycarboxylate water reducer.

[0021] The method for preparing the above-mentioned high-strength permeable brick comprises the following steps:

[0022] Weigh each raw material according to the weight ratio, and mix cement, modified diatomaceous earth, fly ash and crushed stone evenly, then add water reducer and water, stir evenly to obtain a mixture, put the mixture in a mold and press-form it to obtain a blank, and cure the blank in a natural environment for 25-30 days.

[0023] Compared with the prior art, the beneficial effects of the present invention are mainly:

[0024] 1. The present invention first adds the pretreated diatomite to a Tris-dopamine hydrochloride solution, and the dopamine molecules are oxidized and self-polymerized in the solution to form polydopamine molecules. Polydopamine has strong adhesion and film-forming properties, and can form a dense coating layer on the surface of the diatomite particles. This coating layer improves the interaction between the diatomite particles and the cement matrix, thereby improving the overall strength of the material. Secondly, the graphene is silane-modified by γ-aminopropyltriethoxysilane, and the modified graphene containing amino groups interacts with the catechol hydroxyl or amino group on the surface of polydopamine to form hydrogen bonds, which can not only enhance the structural stability of the modified graphene and polydopamine-coated diatomite mixed system, but also improve the compatibility of graphene with the cement matrix, reduce the stress concentration phenomenon of the graphene itself, and thus improve the wear resistance of the material.

[0025] 2. The permeable bricks prepared by the present invention have high compressive strength and flexural strength, good mechanical properties, small grinding pit length, and excellent wear resistance. DETAILED DESCRIPTION

[0026] The technical scheme of the present invention is further described below in conjunction with specific embodiments. However, it should be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be regarded as limiting the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0027] 1. Example

[0028] Example 1

[0029] A high-strength water-permeable brick is composed of the following raw materials in parts by weight: 31 parts of cement, 11 parts of modified diatomaceous earth, 44 parts of fly ash, 75 parts of crushed stone, 4 parts of polycarboxylic acid water-reducing agent, and 8 parts of water.

[0030] Among them, the specific preparation process of modified diatomite is as follows:

[0031] (1) adding diatomaceous earth to a 23% sulfuric acid solution, heating the solution at 75°C for 2.5 hours, adjusting the pH of the reaction solution to neutral after the reaction is completed, filtering and drying the solution to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to a Tris-dopamine hydrochloride solution according to a solid-liquid ratio of 1 g:16 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2.5 g / L, stirring the solution at 53°C for 30 hours, filtering the solution after the reaction is completed, washing with deionized water and drying the solution to obtain polydopamine-coated diatomaceous earth;

[0032] (2) adding graphene to tetrahydrofuran at a mass ratio of 1:0.25, and then adding γ-aminopropyltriethoxysilane, heating at 45°C for 6.5 hours, filtering, washing, and drying after the reaction is completed to obtain silane-modified graphene;

[0033] (3) According to the mass ratio of the polydopamine-coated diatomaceous earth in step (1) to the silane-modified graphene in step (2) of 1:0.1, the polydopamine-coated diatomaceous earth in step (1) and the silane-modified graphene in step (2) are added to anhydrous ethanol, stirred at 45° C. for 3 h, and after the stirring is completed, filtered and dried to obtain modified diatomaceous earth.

[0034] The preparation method of the above-mentioned high-strength permeable brick is as follows:

[0035] Weigh each raw material according to the weight ratio, and mix cement, modified diatomaceous earth, fly ash and crushed stone evenly, then add polycarboxylic acid water reducer and water, stir evenly to obtain a mixture, put the mixture in a mold and press-form to obtain a blank, and cure the blank in a natural environment for 30 days.

[0036] Example 2

[0037] A high-strength water-permeable brick is composed of the following raw materials in parts by weight: 25 parts of cement, 10 parts of modified diatomaceous earth, 40 parts of fly ash, 60 parts of crushed stone, 3 parts of wood sulfonate water reducing agent, and 5 parts of water.

[0038] Among them, the specific preparation process of modified diatomite is as follows:

[0039] (1) adding diatomaceous earth to a 20% sulfuric acid solution, heating the solution at 80°C for 2 h, adjusting the pH of the reaction solution to neutral after the reaction is completed, filtering and drying the solution to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to a Tris-dopamine hydrochloride solution at a solid-liquid ratio of 1 g:10 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2 g / L, stirring the solution at 50°C for 32 h, filtering the solution after the reaction is completed, washing with deionized water and drying the solution to obtain polydopamine-coated diatomaceous earth;

[0040] (2) adding graphene to tetrahydrofuran at a mass ratio of 1:0.2, and then adding γ-aminopropyltriethoxysilane, heating at 50° C. for 6 h, and filtering, washing, and drying after the reaction to obtain silane-modified graphene;

[0041] (3) According to the mass ratio of the polydopamine-coated diatomaceous earth in step (1) to the silane-modified graphene in step (2) of 1:0.05, the polydopamine-coated diatomaceous earth in step (1) and the silane-modified graphene in step (2) are added to anhydrous ethanol, stirred at 40° C. for 4 h, and after the stirring is completed, filtered and dried to obtain modified diatomaceous earth.

[0042] The preparation method of the above-mentioned high-strength permeable brick is as follows:

[0043] Weigh each raw material according to the weight ratio, and mix cement, modified diatomaceous earth, fly ash and crushed stone evenly, then add wood sulfonate water reducer and water, stir evenly to obtain a mixture, put the mixture in a mold and press-form it to obtain a blank, and cure the blank in a natural environment for 28 days.

[0044] Example 3

[0045] A high-strength permeable brick is composed of the following raw materials in parts by weight: 40 parts of cement, 20 parts of modified diatomaceous earth, 50 parts of fly ash, 80 parts of crushed stone, 5 parts of polycarboxylic acid water reducer, and 10 parts of water.

[0046] Among them, the specific preparation process of modified diatomite is as follows:

[0047] (1) adding diatomaceous earth to a 25% sulfuric acid solution, heating the solution at 70°C for 3 h, adjusting the pH of the reaction solution to neutral after the reaction is completed, filtering and drying the solution to obtain pretreated diatomaceous earth; adding the pretreated diatomaceous earth to a Tris-dopamine hydrochloride solution at a solid-liquid ratio of 1 g:20 mL, wherein the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 3 g / L, stirring the solution at 55°C for 28 h, filtering the solution after the reaction is completed, washing with deionized water and drying the solution to obtain polydopamine-coated diatomaceous earth;

[0048] (2) adding graphene to cyclohexane at a mass ratio of 1:0.3, and then adding γ-aminopropyltriethoxysilane, heating at 40°C for 7 hours, filtering, washing, and drying after the reaction to obtain silane-modified graphene;

[0049] (3) According to the mass ratio of the polydopamine-coated diatomaceous earth in step (1) to the silane-modified graphene in step (2) of 1:0.15, the polydopamine-coated diatomaceous earth in step (1) and the silane-modified graphene in step (2) are added to anhydrous ethanol, stirred at 50° C. for 2 h, and after the stirring is completed, filtered and dried to obtain modified diatomaceous earth.

[0050] The preparation method of the above-mentioned high-strength permeable brick is as follows:

[0051] Weigh each raw material according to the weight ratio, and mix cement, modified diatomaceous earth, fly ash and crushed stone evenly, then add polycarboxylic acid water reducer and water, stir evenly to obtain a mixture, put the mixture in a mold and press-form to obtain a blank, and cure the blank in a natural environment for 25 days.

[0052] 2. Comparative Example

[0053] Comparative Example 1

[0054] The difference between Comparative Example 1 and Example 1 is:

[0055] 10 parts of diatomaceous earth and 1 part of graphene are used to replace the modified diatomaceous earth, and the rest is the same as in Example 1.

[0056] Comparative Example 2

[0057] The difference between Comparative Example 2 and Example 1 is that the preparation process of the modified diatomaceous earth is different.

[0058] Specifically, step (1) is omitted, and step (2) is the same as in Example 1;

[0059] Step (3) is to add the pretreated diatomaceous earth and the silane-modified graphene in step (2) into anhydrous ethanol in a mass ratio of 1:0.1, stir at 45° C. for 3 hours, filter and dry after stirring to obtain the product.

[0060] Comparative Example 3

[0061] The difference between Comparative Example 3 and Example 1 is that the preparation process of the modified diatomaceous earth is different.

[0062] Specifically, step (1) is the same as in Example 1, and step (2) is omitted;

[0063] Step (3) is to add the polydopamine-coated diatomaceous earth and graphene in step (1) to anhydrous ethanol in a mass ratio of 1:0.1, stir the anhydrous ethanol at 45° C. for 3 hours, filter and dry after stirring to obtain the product.

[0064] Comparative Example 4

[0065] The difference between Comparative Example 4 and Example 1 is that 10 parts of polydopamine-coated diatomaceous earth and 1 part of silane-modified graphene are used instead of modified diatomaceous earth, and the preparation method of polydopamine-coated diatomaceous earth and silane-modified graphene is the same as that of Example 1.

[0066] 3. Test examples

[0067] The permeable bricks prepared in Examples 1-3 and Comparative Examples 1-4 were made into samples of 10×20×6 cm. The permeability coefficient, compressive strength, flexural strength and grinding pit length of each group of permeable bricks were tested according to GB / T25993-2010. The results are shown in Table 1.

[0068] Table 1

[0069]

[0070] It can be seen from Table 1 that the permeable bricks prepared by the present invention have high compressive strength and flexural strength, good mechanical properties, small grinding pit length, and excellent wear resistance.

[0071] Compared with Examples 1-3, the mechanical properties and wear resistance of the permeable bricks prepared in Comparative Examples 1-4 are reduced to varying degrees. Comparative Example 1 uses diatomite and graphene instead of the modified diatomite of the present invention; Comparative Example 2 does not coat the pretreated diatomite with polydopamine; Comparative Example 3 does not modify the graphene; Comparative Example 4 uses polydopamine-coated diatomite and silane-modified graphene instead of the modified diatomite of the present invention. It can be seen that changing the preparation process of the modified diatomite of the present invention will affect the mechanical properties and wear resistance of the permeable bricks.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A high-strength permeable brick, characterized in that: The raw materials include the following parts by weight: 25-40 parts of cement, 10-20 parts of modified diatomaceous earth, 40-50 parts of fly ash, 60-80 parts of crushed stone, 3-5 parts of water reducing agent, and 5-10 parts of water; The preparation process of the modified diatomite is as follows: (1) adding the pretreated diatomaceous earth to a Tris-dopamine hydrochloride solution for stirring reaction, and after the reaction is completed, obtaining polydopamine-coated diatomaceous earth; (2) adding graphene to a solvent, and then adding γ-aminopropyltriethoxysilane to carry out a heating reaction. After the reaction is completed, filtering, washing, and drying are performed to obtain silane-modified graphene; (3) The polydopamine-coated diatomaceous earth obtained in step (1) and the silane-modified graphene obtained in step (2) are added into anhydrous ethanol, stirred, filtered, and dried to obtain modified diatomaceous earth.

2. The high-strength permeable brick according to claim 1, characterized in that: The solid-to-liquid ratio of the pretreated diatomaceous earth to the Tris-dopamine hydrochloride solution in step (1) is 1 g: (10-20) mL; the concentration of dopamine hydrochloride in the Tris-dopamine hydrochloride solution is 2-3 g / L.

3. The high-strength permeable brick according to claim 1, characterized in that: The pretreatment process of the pretreated diatomaceous earth in step (1) is as follows: adding the diatomaceous earth to a sulfuric acid solution with a concentration of 20-25%, heating it at 70-80° C. for 1.5-3 h, adjusting the pH of the reaction solution to neutral, filtering it and drying it to obtain the pretreated diatomaceous earth.

4. The high-strength permeable brick according to claim 1, characterized in that: The stirring reaction temperature in step (1) is 50-55° C., and the stirring reaction time is 28-32 h.

5. The high-strength permeable brick according to claim 1, characterized in that: In step (2), the mass ratio of graphene to γ-aminopropyltriethoxysilane is 1:(0.2-0.3), and the solvent is tetrahydrofuran or cyclohexane.

6. The high-strength permeable brick according to claim 1, characterized in that: The temperature of the heating reaction in step (2) is 40-50° C., and the heating reaction time is 6-7 hours.

7. The high-strength permeable brick according to claim 1, characterized in that: In step (3), the mass ratio of the polydopamine-coated diatomaceous earth obtained in step (1) to the silane-modified graphene obtained in step (2) is 1:(0.05-0.15).

8. The high-strength permeable brick according to claim 1, characterized in that: The stirring temperature in step (3) is 40-50°C, and the stirring time is 2-4h.

9. The high-strength permeable brick according to claim 1, characterized in that: The water reducer is a wood sulfonate water reducer or a polycarboxylate water reducer.

10. The method for preparing high-strength permeable brick according to any one of claims 1 to 9, characterized in that: The following steps are involved: Weigh each raw material according to the weight ratio, and mix cement, modified diatomaceous earth, fly ash and crushed stone evenly, then add water reducer and water, stir evenly to obtain a mixture, put the mixture in a mold and press-form it to obtain a blank, and cure the blank in a natural environment for 25-30 days.

Citation Information

Patent Citations

  • Preparation method of anti-folding type cement-based waterproof coating

    CN108424082A

  • High-strength recycled concrete and preparation method thereof

    CN111960766A